PLoS Biology Issue Image | Vol. 18(11) December 2020 (PLOS Biology, 2020)
Aequorea's secrets revealed: New fluorescent proteins with unique properties for bioimaging and biosensingUsing mRNA sequencing and de novo transcriptome assembly, Lambert et al. identified, cloned, and characterized nine previously undiscovered fluorescent protein homologs from Aequorea victoria and a related Aequorea species, finding that most sequences were highly divergent from the well-known and widely used A. victoria green fluorescent protein (GFP). Among these fluorescent proteins are the brightest GFP homolog yet characterized and a reversibly photochromic fluorescent protein that responds to UV and blue light. Beyond green emitters, Aequorea species express purple- and blue-pigmented chromoproteins with absorbances ranging from green to far-red, including two that are photoconvertible. X-ray crystallography revealed that Aequorea chromoproteins contain a chemically novel chromophore with an unexpected crosslink to the main polypeptide chain. Because of the unique attributes of several of these newly discovered fluorescent proteins, the authors expect that Aequorea will, once again, give rise to an entirely new generation of useful probes for bioimaging and biosensing. The image shows solutions of five purified recombinant proteins from Aequorea species, illuminated with 480-nm LED (top) and white light (bottom).Image Credit: pbio.3000936